Alkoxyphosphorane/Borane Cooperative Alkylations: A Frustrated Lewis Pair Version of the Mitsunobu Reaction. Issue 23 (15th March 2023) - Chen, Ting; Mei, Yanbo; Liu, Liu Leo; Zhao, Yufen; Wu, Yile; Stephan, Douglas W.
Abstract: The combination of the alkoxyphosphoranes, Ph2 P(OR)(O2 C6 Cl4 ) and the borane B(C6 F5 )3 generates the zwitterions 3 which act as FLP to effect the alkylation of several nucleophiles affording C−C, C−N, C−H and C−Cl coupling products. A DFT study shows the reaction proceeds via an FLP activation pathway generating an alkoxyphosphonium intermediate which effects the alkylation of the nucleophiles, akin to the Mitsunobu reaction. Abstract : Alkoxyphosphoranes, Ph2 P(OR)(O2 C6 Cl4 ) and the borane B(C6 F5 )3 generate zwitterions which act as FLPs to effect the alkylation of nucleophiles affording C−C, C−N, C−H and C−Cl coupling products. A DFT study confirms these reactions proceed via FLP activation pathway, generating an alkoxyphosphonium intermediate and effecting alkylation of the nucleophiles, akin to the Mitsunobu reaction.